2020
DOI: 10.3389/fendo.2020.574662
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Clinical Profiles of Pheochromocytoma and Paraganglioma: A Single Center Study

Abstract: Pheochromocytoma/paraganglioma (PPGL) has a high genetic heterogeneity with 40% germline variants in known pathogenic genes. Data in Chinese on this aspect are scanty. To detect the genetic and clinical profile of Chinese PPGL patients, we examined the variants of 12 known germline pathogenic genes (SDHA, SDHB, SDHC, SDHD, SDHAF2, FH, VHL, RET, NF1, MAX, TMEM127, and KIF1B) by next-generation sequencing and Sanger sequencing in 314 Chinese PPGL subjects. Twenty nine percent of Chinese PPGL patients had germlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 39 publications
4
29
1
Order By: Relevance
“…The overall frequency of germline variants in our study cohort (32.4%) is consistent with that in the reported European cohorts (27.4-32.9%) [5][6][7] and with recent reports in Asians (32.6-34.1%) [22,23,31]. The prevalence of variants in AS presentations vary widely (11.0-36.6%) [6,11,12,18,[21][22][23] depending on the definition of "sporadic" and the number of genes investigated.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overall frequency of germline variants in our study cohort (32.4%) is consistent with that in the reported European cohorts (27.4-32.9%) [5][6][7] and with recent reports in Asians (32.6-34.1%) [22,23,31]. The prevalence of variants in AS presentations vary widely (11.0-36.6%) [6,11,12,18,[21][22][23] depending on the definition of "sporadic" and the number of genes investigated.…”
Section: Discussionsupporting
confidence: 90%
“…This study suggested that the genetic background of PPGL and the associated genotype-phenotype relationship established in Caucasian populations may not apply to Asian populations. It is also worth noting that in the few cohort studies of PPGL in Asia [21][22][23], the profiles of the most common mutated gene and the recurring SDHB variants vary widely by ethnicity even within Asia. In several case reports and case series from Japan, characteristic variants with PPGL have been reported [24][25][26][27][28]; however, there are no comprehensive national studies.…”
Section: Introductionmentioning
confidence: 99%
“…Pheochromocytoma associated with a pathogenic variant occurs at a younger age than pheochromocytoma cases without any mutation ( 8 ). Although there is no clear age limit, having been diagnosed younger than 30–45 may indicate the presence of a mutation.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, molecular pathogenesis of this group of lesions has advanced significantly. Almost 40% of PPGLs patients carry germline mutations in a growing list of genes including SDHA, SDHB, SDHC, SDHD, SDHAF2, VHL, RET, MAX, TEMEM127, FH, NF1, and KIF1B [ 3 , 4 ]. Besides, genes such as EGLN1, EGLN2, MDH2, SLC25A11, MERTK , DLST , and KMT2D are also shown to be related to PPGLs [ 5 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, whole exome sequencing (WES) technology has been employed to detect germline variations of 121 patients who did not have mutations on definite pathogenic genes. In our previous report, the use of next-generation sequencing (NGS) covering SDHA, SDHB, SDHC, SDHD, SDHAF2, VHL, RET, MAX, TEMEM127, FH, NF1, and KIF1B was analyzed in the cohort with 314 PPGL patients [ 3 ]. Among them, four patients showed CHEK2 gene heterozygous mutations.…”
Section: Introductionmentioning
confidence: 99%